2021
DOI: 10.3390/educsci11020059
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Experiences of Online Evaluation in Courses of Civil Engineering during the Lockdown Learning Due to the COVID-19 Pandemic

Abstract: As a consequence of the global health emergency in early 2020, universities had to tackle a sudden shift in their teaching–learning strategies so that the preset competences could be fulfilled. This study presents the learning outcomes of the implemented tasks, student experiences, and feedback, as well as some reflections from the instructors with a holistic perspective of the courses due to the adopted measures and adaptations. Six courses taught at civil engineering degrees of three universities, two from S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 34 publications
3
85
2
5
Order By: Relevance
“…The motivation of a self-directed online learner (curiosity, interest, and intrinsic based self-improvement) (Bonk et al 2015) is noted though individual motivational drivers were not required to answer the research questions. Higher attrition rates associated with online learning as discussed by Stone (2019) and García-Alberti et al (2021) could not realistically be observed in this study as it was not a longitutidanal study. Nevertheless, it was noted that high attrition rates can possibly be mitigated by offering services (personal counselling and mental health/ career guidance) to the online students.…”
Section: Study Limitations and Closing Commentsmentioning
confidence: 79%
“…The motivation of a self-directed online learner (curiosity, interest, and intrinsic based self-improvement) (Bonk et al 2015) is noted though individual motivational drivers were not required to answer the research questions. Higher attrition rates associated with online learning as discussed by Stone (2019) and García-Alberti et al (2021) could not realistically be observed in this study as it was not a longitutidanal study. Nevertheless, it was noted that high attrition rates can possibly be mitigated by offering services (personal counselling and mental health/ career guidance) to the online students.…”
Section: Study Limitations and Closing Commentsmentioning
confidence: 79%
“…In addition, web-based learning has shown several advantages such as economics of scale, novel instructional methods, or flexible scheduling [25]. Among them, the possibility of overcoming barriers of distance has been of special interest during the COVID-19 pandemic situation [26]. Moreover, web-based learning became an attractive alternative for training during several months in most of the developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Web-based learning frameworks have gained presence during the development of digital transformation of universities [28,33]. As students are digital natives, it appears necessary to identify their perspective on the use of technology in the academic context, as well as with what purpose and operations students use the technologies, and to understand what their expectations are [26,34]. At the same time, it seems attainable to harness the benefits of digital media to communicate with them and guide their training.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has affected educational and sports systems worldwide, leading to the near-total closure of schools, universities and collegesand, consequently, the closure of affiliated training centers for young athletes as a measure to curtail the spread of the infectious disease [1][2][3]. Meanwhile, this global health crisis is triggering the application of distance learning modalities in various fields [4], requiring educators to investigate alternative methods with which to enhance knowledge acquisition in these remote environments [5].…”
Section: Introductionmentioning
confidence: 99%